Identification and Whole Genome Sequencing of the First Case of Kosakonia radicincitans Causing a Human Bloodstream Infection - Bhatti, Micah D.; Kalia, Awdhesh; Sahasrabhojane, Pranoti; Kim, Jiwoong; Greenberg, David E.; Shelburne, Samuel A. (Frontiers in Microbiology, 2017)
The taxonomy of Enterobacter species is rapidly changing. Herein we report a bloodstream infection isolate originally identified as Enterobacter cloacae by Vitek2 methodology that we found to be Kosakonia radicincitans using genetic means. Comparative whole genome sequencing of our isolate and other published Kosakonia genomes revealed these organisms lack the AmpC β-lactamase present on the chromosome of Enterobacter sp. A fimbriae operon primarily found in Escherichia coli O157:H7 isolates was present in our organism and other available K. radicincitans genomes. This is the first report of a Kosakonia species, which are typically associated with plants, causing a human infection.